Lentiviral gene delivery to plasmolipin-expressing cells using Mus caroli endogenous retrovirus envelope protein; Biochimie; Vol. 142 - Prokofjeva M. M. Mariya Mikhaylovna; Proshkina G. M. Galina Mikhaylovna; Lebedev T. D. Timofey Dmitrievich; Shulgin A. A. Aleksandr Anatoljevich; Spirin P. B. Pavel Borisovich; Prasolov V. S. Vladimir Sergeevich; Deev S. M. Sergey Mikhaylovich (2017, 2017)
Title screen